"Working in the dark?" investigation of physiological and psychological indices and prediction of back-lit screen users' reactions to light dimming. (December 2020) - Papinutto, Michael; Nembrini, Julien; Lalanne, Denis
Abstract: The advent of back-lit screens in contemporary offices has profoundly impacted the field of visual comfort. Screen users typically fail to adapt to changing environments and often require an individual light quality. To this end, the new approach of human-building interaction in computer science would consider the context of occupants interacting with lights. Within this framework, the proposed study complements existing studies on reactions to light dimming with a more tightly controlled environment and the task difficulty adapted individually. To evaluate the impact of back-lit screens on participants reaction to light dimming, two sets of participants were assigned either to adaptive or fixed screen back-light. All participants undergo three different naturalistic light dimming speeds typically happening at sunset (0.5–2 lux/s). This study uncovers the potential for physiological measurements to indicate visual discomfort and participants' proclivity to react as a function of personal psychological traits. Importantly, results reveal two behaviour categories: reactive and non-reactive, which are related to participant-specific psychological traits and perceptions. Regardless of the group, eye movements convey early indication of discomfort: participants' reactions happen below standard light levels (300 lux) while fixation number shift state above. Together, eye-movements features and visual comfort questionnaires recordings during the initial steady light period predict ramp behaviour category. Physiological and psychological measurements thus appear as candidates for adaptive light control according to idiosyncratic characteristics, displaying opportunities for increased acceptance of energy-efficient automation strategies. Highlights: Reactive and non-reactive behaviours originate from different psychological traits. Both behaviours show different chosen light but the same delta with prior light. Non-adaptive luminance screen delays reactions occurrence. Eye movements convey an early indication of visual discomfort. Baseline surveys and physiological markers predict behaviours accurately.